Cycles of deportability: Threats, fears, and the agency of 'irregular' migrants in Canada. (17th August 2017) - Ellis, Basia D; Stam, Henderikus J
Abstract: In recent decades, migration scholars have challenged reified categories of 'illegal' migrants and observed migrant 'illegalization' and deportability as exploitative sociopolitical processes. Yet, in the move away from studying 'undocumented migrants' as distinct epistemic subjects, we argue that scholars have lost sight of migrants as agents. Consequently, migrant lives are explained in terms of social determinants rather than migrants' intentional acts or cultural meaning systems. This paper shows how a cultural psychological study of migrant 'illegality' can help restore focus on the migrant as situated agent without reifying or legitimizing categories of migrant 'illegality.' To this end, we discuss ethnographic research conducted with Polish 'irregular' migrants living in Toronto and Mississauga in Canada. From a cultural psychological perspective, we examine how these migrants understood and navigated their unique status-related challenges to build meaningful lives in contradictory and precarious conditions. Our research reveals how Polish migrants learn to become 'irregular' as they develop common modes of being suitable for navigating the underground of Canada's Polish Canadian enclave. Importantly, becoming 'irregular' is neither a passive nor unilaterally imposed process but involves discernible psychosocial dynamics characterized by recurrent threats and fears as well as migrants' deliberate attempts to address and overcome these. We discuss these dynamics as cycles of deportability to mark their cyclical and recurrent nature and argue that they are central for the development of migrant 'illegality' and deportability. We conclude by considering the implications of our findings for understanding agency in the context of migrant 'illegalization.'